2021
DOI: 10.3390/robotics10010024
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Social Robots in Education: Enthusiast, Practical, Troubled, Sceptic, and Mindfully Positive

Abstract: While social robots bring new opportunities for education, they also come with moral challenges. Therefore, there is a need for moral guidelines for the responsible implementation of these robots. When developing such guidelines, it is important to include different stakeholder perspectives. Existing (qualitative) studies regarding these perspectives however mainly focus on single stakeholders. In this exploratory study, we examine and compare the attitudes of multiple stakeholders on the use of social robots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…This might be due to the relatively simple, not highly personalized child robot interaction currently used in schools. In other studies, privacy has been reported to be a major issue related to social robots in education (Sharkey, 2016;Smakman et al, 2021a). Data collection allows personalized interaction, which is one of the key benefits, according to scholars (Kanda et al, 2012;Shimada et al, 2012;Jones et al, 2017;Jones and Castellano, 2018;Woo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be due to the relatively simple, not highly personalized child robot interaction currently used in schools. In other studies, privacy has been reported to be a major issue related to social robots in education (Sharkey, 2016;Smakman et al, 2021a). Data collection allows personalized interaction, which is one of the key benefits, according to scholars (Kanda et al, 2012;Shimada et al, 2012;Jones et al, 2017;Jones and Castellano, 2018;Woo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although social robots show potential as learning or teaching companions for children, according to a recent literature review (Johal, 2020), other studies on the use of social robots in education have reported that it is too early to conclude that robots are, for instance, effective as language tutors (van den , or more effective than human teachers or other types of technology (Woo et al, 2021). Furthermore, both scholars (Sharkey, 2016;Woo et al, 2021) and stakeholders (Smakman et al, 2021a) have voiced concerns related to social robots potentially harming children's social-emotional development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolksdorf et al [67] mapped ethical concerns of applying robots in Kindergarten settings and thereby emphasize, among other aspects, the vulnerability of children as a group and the role of stakeholders (i.e., teachers and caregivers). Smakman et al [66] systematically analyzed the moral and ethical considerations of various stakeholder groups that come with the implementation of robot tutors in education. They compared stakeholders' concerns related to the values of friendship and attachment, human contact, privacy, safety, and so on.…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…Once the educational role of the robot is decided, it is necessary to consider the moral guidelines for its responsible implementation (Smakman et al, 2021), which should be established according to the social environment and in consideration of people's different perspectives. The ethical evaluation (at least for the present time) should be specific to the robot (its capabilities and appearance) and the practice within which it has been placed (van Wynsberghe, 2016).…”
Section: Social Robotics and Educationmentioning
confidence: 99%